2017
DOI: 10.1177/1469066717721484
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution mass spectra processing for the identification of different pathological tissue types of brain tumors

Abstract: The purpose of the work is to demonstrate the possibilities of identifying the different types of pathological tissue identification directly through tissue mass spectrometry. Glioblastoma parts dissected during neurosurgical operation were investigated. Tumor fragments were investigated by the immunohistochemistry method and were identified as necrotic tissue with necrotized vessels, necrotic tissue with tumor stain, tumor with necrosis (tumor tissue as major), tumor, necrotized tumor (necrotic tissues as maj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
(28 reference statements)
0
8
0
3
Order By: Relevance
“…Расхождение в 50% идентификаций можно объяснить различием в методах микроэкстракции и ионизации, используемых разными группами, а также гетерогенностью и биологической вариабельностью образцов. Тем не менее результаты измерений являются воспроизводимыми, что позволяет использовать метод для создания классификаторов тканей по масс-спектру смеси экстрагированных из ткани веществ [15,16].…”
Section: современные возможности масс-спектрометрии в нейроонкологииunclassified
See 2 more Smart Citations
“…Расхождение в 50% идентификаций можно объяснить различием в методах микроэкстракции и ионизации, используемых разными группами, а также гетерогенностью и биологической вариабельностью образцов. Тем не менее результаты измерений являются воспроизводимыми, что позволяет использовать метод для создания классификаторов тканей по масс-спектру смеси экстрагированных из ткани веществ [15,16].…”
Section: современные возможности масс-спектрометрии в нейроонкологииunclassified
“…Жванский и соавт. [15], исследовавшие данным методом биоптаты глиобластомы, показали, что метод анализа липидных профилей может быть положен в основу подхода к анализу состава гетерогенного образца опухолевой ткани, включающей клетки интактной или некротической ткани. В результате такого анализа были разработаны классификационные критерии для определения наличия в образце различных типов ткани, прежде всего интактной мозговой и опухолевой.…”
Section: современные возможности масс-спектрометрии в нейроонкологииunclassified
See 1 more Smart Citation
“…Ambient ionization mass spectrometry allows rapid analysis of samples to detect various mixture components, pathogens and disease biomarkers 912 . In particular, it has been shown that brain tissue samples can be classified based on their lipid profiles; this technique is promising in terms of speeding up and improving the accuracy of analysis of biopsy material obtained during neurosurgery 1319 . However, in order for mass spectrometry methods to be introduced into routine clinical procedure, all stages of the analysis need to be simplified and automated.…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in the uptake (which is limited by the hypovascularity of cancer tissue), synthesis (by activation of de novo synthesis) and consumption (including beta-oxidation pathways) of various fatty acids in malignant cells 1719 result in substantial changes in the cell lipid composition; therefore, many attempts are made to implement lipid profiling for tumor tissue boundary determination 1517,2023 . Mass-spectrometric molecular profiling and identification of tissue is now rapidly developed worldwide due to its high sensitivity and versatility 2428 . Regarding brain tumors and neurosurgery, the most important methods are based on ambient mass spectrometry, or so-called direct tissue analysis, especially on desorption electrospray ionization 11,25 , rapid evaporative ionization 29 or microextraction followed by electrospray ionization 30–32 .…”
Section: Introductionmentioning
confidence: 99%